Odpowiedzi

2009-11-30T18:28:40+01:00
A) (c-1)(b+2)+2bc=cb+2c-b-2+2bc=2-b+3cb
b) (1-b)(b-4)+3b=1b-4-b²+4b+3b=8b-4-b²
c) (2a-n)(a-2b)+5a²=2a²-4ab-na+2nb=2a²-4ab-na+2nb
d) (b-4)(b-3)-b(b+3)=b²-3b-4b+12-b²+3b=-4b+12
e) -(a-b)-5(a-2)(b+1)= -a+b-5(ab+a-2b-2)=-a+b-5ab+5a-10b-10=-5ab+4a+11b-10
f) x(y+2)+(3x+4-y)(y+4)=yx+2x+3xy+12x+4y+16-y²-4y=4xy+14x+16-y²
1 5 1
2009-11-30T18:31:09+01:00
A)
(c-1)(b+2)+2bc=
cb+2c-b-2+2bc=
3cb+2c-b-2

b)
(1-b)(b-4)+3b=
b-4-b²+4b+3b=
8b-4-b²

c)
(2a-n)(a-2b)+5a²=
2a²-4ab-na+2bn+5a²=
7a²-4ab-na+2bn

d)
(b-4)(b-3)-b(b+3)=
b²-3b-4b+12-b²-3b=
-10b+12

e)-(a-b)-5(a-2)(b+1)=
-(a-b)-5(ab+a-2b-2)=
a+b-5ab-5a+10b+10=
-4a+11b-5ab=10

f)
x(y+2)+(3x+4-y)(y+4)=
xy+2x+3xy+12x+4y+16-y²-4y=
4xy+14x+16-y²

Proszę ;)
1 5 1
2009-11-30T18:33:28+01:00
A) (c-1)(b+2)+2bc = cb+2c-b-2+2bc= 3cb+2c-b-2
b) (1-b)(b-4)+3b= b-4-b²+4b+3b= 8b-b²-4
c) (2a-n)(a-2b)+5a²= 2a²-4ab-an+2bn+5a²=7a²-4ab-an+2bn
d) (b-4)(b-3)-b(b+3)=b²-3b-4b+12-b²-3b=-10b+12
e)-(a-b)-5(a-2)(b+1)=-a+b-5(ab+a-2b-2)=-a+b-5ab-5a+10b+10=-6a+11b-5ab+10
f)x(y+2)+(3x+4-y)(y+4)= xy+2x+3xy+12x+4y+16-y²-4y=14x+4xy-y²+16
1 5 1